Child and adolescent diabetes as a social medicine challenge in Poland - Konwant, Dawid; Kurdyś-Bykowska, Paulina; Armatys, Aleksandra; Stencel-Gabriel, Krystyna (Journal of Education, Health and Sport, 2024)
Introduction: Diabetes prevalence among children and adolescents poses a significant challenge to health care systems worldwide. Insufficient control of lifestyle diseases, including diabetes, can lead to an increased need for the use of outpatient services and hospitalization to stabilize the course of the disease. Aim and methods: Demonstrate type 1 diabetes as an interdisciplinary problem of civilization diseases combining diagnosis and treatment along with the costs incurred by the health care system. Analysis of data on the amount of health services provided and costs for type 1 diabetes of children and adolescents in 2016-2019 in Poland was made. Results: The number of pediatric patients who received services with the diagnosis E10 increased by 9.6% in the analyzed interval of years. The cost of health services provided increased by 27.2% during this period. The average annual cost of health services per patient in the last year of analysis (2019) increased by 16%. Conclusions: Educational activities should be intensified among children and adolescents to increase proper diabetes self-management. This intervention will reduce the impact of diabetes, which results in increased use of health services to stabilize the disease and its effects.